1999
DOI: 10.1017/s0043174500090731
|View full text |Cite
|
Sign up to set email alerts
|

Relative influence of crop rotation, tillage, and weed management on weed associations in spring barley cropping systems

Abstract: Generalizations concerning the effects of management practices on weed community dynamics often lack robustness, most likely because of the concomitant effects of agronomic and environmental factors. However, such generalizations, when valid, provide useful grounds for predictions and are thus desirable. This study attempted to evaluate the relative importance of crop rotation, tillage, and weed management as factors affecting weed communities and tested the hypothesis of an association between management prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 21 publications
1
36
0
Order By: Relevance
“…(1997). Légère & Samson (1999) reported that dominance of certain weeds in particular cropping systems is highly dependent on the interactions of locations, herbicide management, tillage system and crop sequence. Similarly, Doucet et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(1997). Légère & Samson (1999) reported that dominance of certain weeds in particular cropping systems is highly dependent on the interactions of locations, herbicide management, tillage system and crop sequence. Similarly, Doucet et al .…”
Section: Resultsmentioning
confidence: 99%
“…Hume (1982) documented differences between weed communities in summer fallow–wheat rotation and continuous wheat. Légère & Samson (1999) explained that species dominance in various cropping systems was influenced by interactions among crop rotation, weed management intensity and tillage. Swanton et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, if data are available for more than one management regime, then simulations can examine the implications of rotations of management conditions (Cussans & Moss, 1982). However, prediction of the shifts in weed communities is inherently difficult due to the complex interactions involved (Derksen et al, , 2002Légère & Samson, 1999). Specific responses of weeds to management practices are difficult to generalise because of incomplete understanding of the biology of some weed species, the numerous confounding of factors in cropping systems studies, and the impact of environmental factors.…”
Section: Predicting Weed Shifts Using Simulation Modelsmentioning
confidence: 99%
“…Integrating more than one conservational practice may improve sustainability, while offering the potential for reducing problems caused by a single conservational practice. Some studies have examined the effects of combinations of: tillage systems and weed management on dominant species (Légère & Samson 1999); tillage systems and fertilization sources and rates on species diversity and composition (Stevenson et al . 1997; Swanton et al .…”
Section: Introductionmentioning
confidence: 99%